Describing immovable monuments with metadata standards. (1st January 2012) - Agathos, Michail; Kapidakis, Sarantos
Collections with immovable monuments are less researched than other material of our culture from the aspect of description. This led us to study the metadata elements hosted in various heterogeneous schemas by local inventories, used to describe different types of immovable monuments. In order to achieve some form of semantic interoperability, a series of crosswalks was defined among a derived schema hosting metadata elements from various inventories and official metadata standards that are used to describe architectural works. This allowed us to identify which of these schemas would better fit in these records, in order to reduce semantic heterogeneity. We also highlight weaknesses and adequacies of these standards in the description of immovable monuments, placing particular emphasis in the inevitable semantic gap. Finally, a quantitative measure was defined for the degree of different types of coverage of a source schema by a target schema in order to evaluate the appropriateness of standards.